A training experience for professors of the University of Cagliari - Diletta Peretti; Raffaela Tore (Firenze University Press, 2018)
Nowadays the learning systems are involved in a profound reform to find a common framework of skills to promote employability and active citizenship. The university is called to cultivate innovative methods and pedagogies with the aim of an inclusive education and to be more consistent with an actual development of learning skills, for the perspective of lifelong learning. This paper reports the experience of the "Discentia" project whose purpose is to improve the teaching professionalism of researchers and professors of the University of Cagliari for the educational success of students. Un'esperienza di formazione dei docenti universitari di Cagliari Oggi i sistemi di apprendimento sono impegnati in una profonda riforma per individuare un quadro comune di capacità e competenze funzionali all'occupabilità e alla cittadinanza attiva. Anche l'università è chiamata ad investire in metodi e pedagogie innovative per una educazione inclusiva e un apprendimento più coerente con lo sviluppo di competenze nell'ottica del lifelong learning. Questo contributo riporta l'esperienza del progetto "Discentia" che mira a coltivare la professionalità, come docenti, dei professori e ricercatori dell'Università degli Studi di Cagliari per il successo formativo degli studenti.